Preparing fish protein concentrate from ray fish by water and alkaline hydrolysis and their physiochemical and microbial properties - Al-Hassoon, Ahmed Sh.; Al-Hamadany, Qusay H.; Mohammed, Ameer A. (Mesopotamian Journal of Marine Sciences, 2021)
The present study aims to produce protein concentrate from Ray fish Himantura randalli. Fish samples were brought from the Iraqi seawater (Fao region), two methods of hydrolysis were used, the first with distilled water and the second with alkali solution (NaOH 0.1N) to recover protein concentrates from fish samples. The yield of protein concentrates recovered by distilled water and alkali solution were 7.2% and 10.1%, respectively, the protein content in the produced concentrates were 82.33% and 84.25% and the fat contents were 6.05% and 7.12% in the mentioned methods, respectively. The study has also tested the functional properties of the produced concentrates, (Solubility, water absorption and fat bending), the measurements of these properties were 60.8%, 67.1%; 3, 2.5 ml/gm and 3.5, 3 ml/gm for the two produced concentrates, respectively. The two concentrates have brown color with light fishy smell and showed good storage ability after 60 days under 28 °C and 7 °C without changes in color or smell, it also showed low total bacterial counts which were 429, 386 CFU/gm and 368, 357 CFU/gm for the two concentrates, respectively.